Corrosion Performance and Tribological Properties of Carbonitrided 304 Stainless Steel - El-Rahman, A.M. Abd; El-Hossary, F.M.; Prokert, F.; Negm, N.Z.; Pham, M.T.; Richter, E. (IntechOpen, 2012)
None